Anaerobic threshold and critical velocity parameters determined by specific tests of canoe slalom: Effects of monitored training - Manchado-Gobatto, F. B.; Arnosti Vieira, N.; Dalcheco Messias, L. H.; Ferrari, H. G.; Borin, J. P.; de Carvalho Andrade, V.; Terezani, D. R. (Science & Sports, 2014)
Summary: The aims of study were to determine the anaerobic threshold (AT) and critical velocity (CV) parameters using specific test for canoe slalom and verify the effects of 7-weeks of monitored training on these parameters. Methods: Well-trained kayakers were submitted to specific tests on a lake before and after training. The AT was determined by a progressive kayak "shuttle" exercise (50-m course, 3 min/stage, 5.0-9.5 km.h-1). The blood lactate (BLC) was determined after each stage and AT was obtained using visual inspection and the intersection of the bi-segmental linear regressions. The CV protocol consisted of four maximal paddling exercises (150-600 m). The slope and y-intercept of the `distance vs. time` model were CV and anaerobic paddling capacity (APC). The training intensity sessions were obtained by the rating of perceived exertion (RPE) and the product of daily volume and RPE was the load training. Results: The AT and CV were not different in initial tests (6.7 ± 0.2 and 6.8 ± 0.1 km.h-1). After program, the AT increased (7.3 ± 0.2 km.h-1) without modified CV (6.7 ± 0.0 km.h-1). Conclusion: The AT protocol detected aerobic capacity increase after 7-weeks of training with small changes in load. Thus, the progressive test seems more appropriate to evaluate the effects oftraining on slalom kayakers.